2018
DOI: 10.3390/geosciences8120471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phosphorus in Growth Media on Biomineralization and Cell Surface Properties of Marine Cyanobacteria Synechococcus

Abstract: Through geological time, cyanobacterial picoplankton have impacted the global carbon cycle by sequestrating CO2 and forming authigenic carbonate minerals. Various studies have emphasized the cyanobacterial cell envelopes as nucleation sites for calcium carbonate formation. Little is known, however, about how environmental conditions (e.g., nutrient content) trigger a cell surface and its properties and, consequently, influence biomineralization. Our study aims to understand how phosphorus (P) concentration imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Curiously, this low affinity phosphate transporter was present in SC 5.2 isolates originating from lakes (Atexcac, La Cruz, Aljojuca) undergoing calcium carbonate precipitation phenomena where P concentration drastically drops below the limit of detection [ 58 , 70 , 71 ]. On the other hand, biomineralization experiments have shown that P can strongly affect the molecular composition of the Synechococcus cell surface, which in turn impacts CaCO 3 precipitation [ 72 ]. Hence, a role for inorganic phosphate transporters in this process of carbon precipitation is conceivable.…”
Section: Resultsmentioning
confidence: 99%
“…Curiously, this low affinity phosphate transporter was present in SC 5.2 isolates originating from lakes (Atexcac, La Cruz, Aljojuca) undergoing calcium carbonate precipitation phenomena where P concentration drastically drops below the limit of detection [ 58 , 70 , 71 ]. On the other hand, biomineralization experiments have shown that P can strongly affect the molecular composition of the Synechococcus cell surface, which in turn impacts CaCO 3 precipitation [ 72 ]. Hence, a role for inorganic phosphate transporters in this process of carbon precipitation is conceivable.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 123.6 eV and 126 eV in the Al2s plot of the MBI sample (Fig.10 (d)) could be due to the adsorbed halogen-containing compounds from NLE[27]. The C1s spectra for the MB samples (Fig.11 (a)) show a peak at 284.8 eV related to the C-C group which was observed in many studies related to DD biofilm and has been attributed to the presence of amino acids[28,29]. The carbon spectra for the MBI sample (Fig.11 (b)) show a prominent signal at 288.9 eV due to the carboxylic or ester groups.…”
mentioning
confidence: 70%
“…Traditionally, anionic functionalities are thought to increase interfacial energy (relative to neutral macromolecules) due to their hydrophilicity [14,27]. However, few nucleation studies have been conducted involving phosphorylated macromolecules despite their biological significance [79,80]. To resolve these findings, Akkineni et al applied molecular dynamics (MD).…”
Section: Modulating Atomic-level Macromolecule-ca 2+ Interactions To ...mentioning
confidence: 99%